Unreal development kit game design cookbook : over 100 recipes to accelerate the process of learning game design with UDK. - Mooney, Thomas, ....- (Birmingham : Packt, 2012)
Chapter 1: Heads Up-UDK Interface Essentials Chapter 2: Notes From an Unreal World-Constructing Game World Elements Chapter 3: It Lives!-Character Setup and Animation Chapter 4: Got Your Wires Crossed?-Visual Scripting of Gameplay in Kismet Chapter 5: It Is Your Destiny!-Scripting Complex Gameplay Flow in Kismet Chapter 6: Under The Hood-Configuration and Handy Tweaks for UDK Chapter 7: Hi, I'm Eye Candy!-Ways to Create and Use Particle Effects Chapter 8: Then There Was Light!-Manipulating Level Light and Shadows Chapter 9: The Devil Is In The Details!-Making the Most of Materials Chapter 10: The Way Of The Flash UI-Scaleform, CLIK, and Flash Interfaces